Desain UI/UX Aplikasi Pembelajaran Agama Islam bagi Mualaf Menggunakan Metode Five Planes - Ilham Ismail; Dhian Satria Yudha Kartika; Anindo Saka Fitri (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
A muslim revert must be given guidance to learn more about his religion, as well as basic Islamic education to increase faith. This situation makes muslim revert need Islamic religious education learning media to accommodate the strong desire to learn, including basic Islamic material, worship guides, how to read the Quran, Muslim communities, guidance, etc. The purpose of this research is to design an Islamic learning application for muslim revert using the Five Planes method that produces good usability testing. This research will discuss the creation of a religious learning application interface design using the Five Planes method which focuses on human interests to solve problems and create new innovations, testing in this study was carried out based on recommendations from ISO 9241-11.. The final test score after two iterations. The result is that effectiveness gets 89.23% and efficiency gets 90% for five converts, and effectiveness 89.26% and efficiency 80.65% for five counselors, for satisfaction using SUS reaches a value of 77.5, and QUIS reaches 7.88 for converts and 6.60 for counselors. The test results obtained a good or good assessment.